Perception of knowledge of product demand and perception towards economic interdependence in the Queral village, Caraz , Ancash - Paredes T., Mildred (2007)
Objectives: To identify the perception of Queral Small village’s members towards the 1) formation of economic interdependent relations and the perception of knowledge about the demand of its products of the Queral Small village, 2) To know the relation between the perception of knowledge the demand of products with economic perceptions interdependence in the sample of 51 members, a representing one by greater family of 14 years of the Queral Small village. Design: Correlational applied investigation. Material and methods: Data collected with two scales: Scale of Perception to the Economic Interdependence that measures three independent factors, and the Scale of Perception to the knowledge to the demand, measures from 6 factors with a trustworthiness of 0,93. Results: The knowledge of the demand is low, whereas the perception of the interdependence is favorable. One was 5 significant but inverse correlations between components of these factors with the exception of the relation between the Perception of the Knowledge of the Supply of Products with Perception towards the economic Interdependence by the Perception of the Supply (0,29). The component rest do not correlate to each other. Conclusion: Not significant relation (-0.05) between the Perception of the Knowledge of the Demand with Perception towards the Economic Interdependence in the Queral Small village in Caraz, Ancash.